Pengaruh kekuatan mata pisau mesin pencacah kompos menggunakan metode finite element analysis - Aji Abdillah Kharisma; Mahesa Dikta Ajiwiratama (Jurnal Teknik Mesin Indonesia, 2023)
Garbage is solid waste consisting of organic and inorganic substances which are considered unusable and must be managed so as not to endanger the environment, especially to compost waste. Compost is a process of fermentation ultimate product from a pile of garbage or part of plants (straw, grass, banana leaves, sugarcane leaves, etc.). The blade is the essential component in chopping process of the compost chopper. The method analysis of the knife blade design model simulation is conducted to analyze the performance of the knife blade based on the given loading force. Modeling simulation is conducted using software-based applications and will be strengthened by theoretical comparisons. The knife blade material type is SS41, and the axle is S45C.The results obtained from the design modeling analysis using software include the maximum stress (von misses stress) at loading of 2.5 N for every 24 knife blades, the total is 157 MPa, the displacement result is 0.161 mm, and also the safety factor is 3.05, meanwhile the theoretical calculation result of von misses stress is 168 MPa, displacement 0.03 mm, and safety factor is 3.18. Based on the results of value safety factor analysis of knife blade design, it can be continued to the process stage manufacturing.